Diagnosing diagnostic language assessment. (July 2015) - Lee, Yong-Won
Diagnostic language assessment (DLA) is gaining a lot of attention from language teachers, testers, and applied linguists. With a recent surge of interest in DLA, there seems to be an urgent need to assess where the field of DLA stands at the moment and develop a general sense of where it should be moving in the future. The current article, as the first article in this special issue, aims to provide a general theoretical background for discussion of DLA and address some fundamental issues surrounding DLA. More specifically, the article (a) examines some of the defining characteristics of DLA and its major components, (b) reviews the current state of DLA in conjunction with these components, and (c) identifies some promising areas of future research and development of DLA where important breakthroughs can be made in the future. Some of the major obstacles and challenges facing DLA are identified and discussed, along with some possible solutions to them.